The Modified Gil-Vernet Antireflux Surgery: A Successful Technique for High-Grade Vesicoureteral Reflux Correction in Children—Long-Term Follow-Up - Mahmoudreza Moradi; Abolhassan Seyedzadeh; Saeed Gharakhloo; Aref Teymourinezhad; Kaveh Kaseb; Haress Rezaee (Advances in Urology)
Introduction. Vesicoureteral reflux (VUR) is a common urologic anomaly in children. Many techniques have been offered to manage this condition, in which one of them is modified Gil-Vernet antireflux surgery. The study fullfiled to evaluate the efficacy and safety of modified Gil-Vernet antireflux surgery in correction of high-grade VUR. Materials and Methods. A retrospective study in which we evaluated efficacy, safety, and complications of modified Gil-Vernet antireflux surgery as a choice procedure for high-grade reflux in all patients who underwent it since 2000 to 2016 at 2 hospitals of Kermanshah University of medical sciences that all of them were done by one surgeon. Results. 183 patients with 290 high-grade refluxing units (grade IV or V) were reviewed. 182 refluxing units were grade IV, and 108 units were grade V. There were 76 (41.54%) patients with unilateral and 107 (58.46%) patients with bilateral VUR. Reflux in high-grade group corrected completely in 278 (95.86%) refluxing units and 175 patients (95.62%). Conclusions. Our results are remarkable and compatible with other techniques’ results. This simple and safe technique can correct bilateral VURs simultaneously; thus, it is rational to be considered for high-grade VUR correction. According to our results, we suggest the modified Gil-Vernet antireflux procedure for high-grade VUR correction as a simple, safe, and successful technique. This trial is registered with 67145/86/1233.